Ayurvedic Management of Vicharchika (Dry Eczema) (International Journal of Ayurveda and Pharma Research, 2023)
Skin disorders are major health issues in the present era. It is a multifaceted concept that includes the emotional, social, and economic impacts on individuals, their families, and society as a whole. All skin conditions are classified as "Kushta" in Ayurveda, which is further divided into Mahakushta and Kshudra Kushta. Vicharchika is explained by Acharya charak in Kshudra kusta. In Ayurveda, Vicharchika is a Rakta Pradoshaja Vikara, involving three Doshas with Kapha predominance. A patient of 40 years, old man consulted in OPD of Kaya Chikitsa department, Sir Sundarlal Hospital, IMS, BHU. Patient was presented with complains blackish reddish patches with tearing of skin along with burning sensation and itching on both the hands with involvement of fingers since 8 yrs. Patients was treated on line of Rakta Pradoshaja Vikara and Dosha dominance. Patient was givens Saman aushadi like- Aarogyavardhini Vati, Kaishor Guggulu, Panchtikta Ghrit Guggulu, Patolakatukrohini Kashaya and Lepa of Sidharthak Churna with water and 2 sitting of Jalaukavacharan. The results of the treatment are recorded as a photographic document, As per the result lesions of the skin became lighter in colour and erythema and itching was completely gone. With the help of Ayurvedic treatment we can completely cure this disease with proper medication and diet management.